Violência Sexual: é preciso vencer o medo e enfrentar o problema - P. Gawryszewski, Vilma; Hidalgo, Neuma; Heloísa Santos Bueno, Stella Maris; Lerner, Theo; Mochon da Costa Alves, Maria Cecília; Boulos, Ivete; Vieira Seron, Maria Denize; Swaim Muller, Adriana; Drezett, Jefferson; da Costa, João Carlos; et al. (BEPA. Boletim Epidemiológico Paulista, 2004)